SOSIALISASI SEKOLAH DASAR TV SEBAGAI MEDIA PEMBELAJARAN MASA PANDEMI COVID-19 DI SDN 1 RAWAK - Imanuel Sairo Awang; Eliana Yunitha Seran; Gabriel Serani (STKIP Persada Khatulistiwa Sintang, 2022)
Based on a letter from the Ministry of Education and Culture (Kemendikbud) concerning Guidelines for Implementing Learning from Home in the Emergency Period of the Spread of Covid-19, it is explained that the purpose of implementing Belajar Dari Rumah (BDR) is to ensure the fulfillment of students' rights to obtain education services during an emergency Covid-19. Therefore, the local authorities through the dinas pendidikan adopted a separate policy in the form of limited face to face learning. Implementation of BDR by holding a face to face learning process faces challenges in terms of providing interesting and fun learning resources. One that can be applied is to develop learning media that are interesting and fun and can be reached both online and offline. Various interactive learning media are available in various forms, one of which is already available on the Sekolah Dasar TV on youtube platform page. With the presence of Sekolah Dasar TV through the youtube page, it is hoped that it will be able to produce learning interactions like in the classroom.Key words: media, pandemic.